2017
DOI: 10.1007/s11065-017-9354-4
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Levels of Atypical Handedness in Autism: Meta-Analyses

Abstract: An elevated prevalence of atypical handedness (left-, mixed-, or non-right-handedness) has been repeatedly reported in individuals with Autism Spectrum Disorder (ASD) compared to typically developing individuals. However, the exact magnitude of this difference as well as the presence of possible moderating factors remains unknown. Here, we present three sets of meta-analyses of studies that assessed the handedness prevalence among individuals with ASD, totaling 1199 individuals (n = 723 individuals with ASD an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
97
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(101 citation statements)
references
References 141 publications
4
97
0
Order By: Relevance
“…Importantly, large-scale, highly-powered meta-analyses can help address the reproducibility issues that are at the forefront of scientific discussion within psychological research (e.g., Open Science Collaboration, 2015). Indeed, a number of publications have recently used meta-analysis to summarize the field of handedness (e.g., Ntolka & Papadatou-Pastou, 2018;Markou, Ahtam, & Papadatou-Pastou, 2017; see also Papadatou-Pastou, 2018).…”
Section: Human Handedness: a Meta-analysismentioning
confidence: 99%
“…Importantly, large-scale, highly-powered meta-analyses can help address the reproducibility issues that are at the forefront of scientific discussion within psychological research (e.g., Open Science Collaboration, 2015). Indeed, a number of publications have recently used meta-analysis to summarize the field of handedness (e.g., Ntolka & Papadatou-Pastou, 2018;Markou, Ahtam, & Papadatou-Pastou, 2017; see also Papadatou-Pastou, 2018).…”
Section: Human Handedness: a Meta-analysismentioning
confidence: 99%
“…Resting state functional magnetic resonance imaging (MRI) data have also shown a generally rightward shift of asymmetry involving various functional networks of brain regions (15). In addition, people with ASD have a higher rate of left-handedness than the general population (14,16,17). Furthermore, an electroencephalography study reported that infants at high risk for ASD showed more rightward than leftward frontal alpha asymmetry at rest (18).…”
Section: Introductionmentioning
confidence: 99%
“…For example, personality traits and cognitive skills have been claimed to associate with handedness (Peterson and Lansky, 1977;Sartarelli, 2016). The prevalence of non-right-handedness has also been found to be increased in people with various cognitive or psychiatric disorders (Deep-Soboslay et al, 2010;Markou et al, 2017).…”
Section: Introductionmentioning
confidence: 99%